PROFITABILITY ANALYSIS OF PROPERTY AND REAL ESTATE COMPANIES - nurmardianti, siti; Suwaidi, Rahman Amrullah (Jurnal Ekonomi Balance, 2021)
Profitability is a very important factor to determine whether a company is very good or bad, as well as its ability to generate profits. Relatively high and stable profits can encourage investors to invest in the company. This study aims to analyze the effect of leverage proxied by debt to equity ratio, activity ratio proxied to total assets turnover, and sales growth to profitability in property and real estate companies. listed on the Indonesia Stock Exchange for the period 2017-2019. The technique of determining the sample in this study used purposive sampling. The sample used is 45 property and real estate companies registered with Bersa Efek Indonesia for the 2017-2019 period. The type of data used in this study is secondary data in the form of annual financial reports of property and real estate companies for the period 2017-2019 which have been published and obtained via the internet through the website address www.idx.co.id. The method of analysis using multiple linear regression analysis with SPSS program. Hypothesis testing used is the coefficient of determination, simultaneous test (F test) and partial test (t test). , classic assumption test, namely normality and multicollinearity test, heteroscedasticity test, autocorrelation test. Based on the results of the analysis that has been done, it can be concluded that (1) Leverage does not contribute to Profitability, (2) Activity Ratio contributes to Profitability, (3) Sales growth does not contribute to Profitability.